CuO, MgO, and ZrO2 Loading on HZSM5 by Deposition-precipitation: Study of Crystallinity, Specific Surface Area, and Morphology - Rizky Ibnufaatih Arvianto; Anatta Wahyu Budiman; Khoirina Dwi Nugrahaningtyas (Universitas Gadjah Mada, 2022)
Bifunctional catalysts are often used in multiple reactions to synthesize certain products. The catalytic activity of bifunctional catalysts is influenced by parameters such as crystallinity, specific surface area, metal distribution, and morphology. Bifunctional catalysts are manufactured by adding metal to the support. The metal loading to the support often affects these parameters. Therefore, this research was conducted to determine the effect of CuO, MgO, and ZrO2 addition to HZSM5 on these parameters. The often-used loading method was deposition precipitation. The pH of the metal-support precursors' solution was increased to basic (pH of 8) to deposit the metal on the support. The loading effect was investigated by producing the following materials: CuO/HZSM5, CuO/ZrO2/HZSM5, CuO/MgO/HZSM5, and CuO/MgO/ZrO2/HZSM5. Each material was characterized using XRD, SAA, SEM, Mapping, EDS, and XRF. The results showed that all metal oxides could be embedded in the HZSM5. The loading of CuO, MgO, and ZrO2 to HZSM5 did not affect the crystallinity (structure) and morphology, increased the specific surface area, and was evenly distributed inside the pore of HZSM5. Further research is needed to determine the effect of crystallinity, specific surface area, and morphology on other metals and support types.